The impact of micro and macro-economic factors on the profitability of banks: a case of Zimbabwean banking sector (2012-2016) - Samanyanga, Tinashe (Midlands State University, 2018)
The research sought to establish the impact of micro and macro-economic factors on the profitability of banks in the banking sector of Zimbabwe. The low levels of profitability has been an area of concern. The study covered the period from 2012 to 2016 using monthly time series data employing the Ordinary Least Squares method to ascertain the factors that contribute to profitability as measured by Return on Assets. In the previous period, the profitability of banks have been on an upward trend despite the cash shortages. The major research findings and conclusions is that inflation has a negative impact and Gross domestic Product has a positive impact on the profitability of banks and on Micro economic factors Capital adequacy, Deposits and Liquidity they are all significant at 5% in explaining the profitability of banks. However, Total Equity to total Assets was found not to be significant at 5% and Interest rate was found to be inversely related to the Profitability of banks. The research concluded by urging the government to craft policies that can increase economic growth and continue to use the multicurrency so as to keep inflation low.